2017
DOI: 10.25103/jestr.103.04
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Dynamic Modeling Method of Articulated Vehicles

Abstract: Most of the existing research related to the handling stability of articulated vehicles takes the front wheel angle as input and neglects the influence of the steering system and regards these vehicles as moving in planes that parallel the ground plane. The established dynamic model cannot meet the requirements of stability control under unmanned and high-speed working conditions. This research proposed a fusion modeling method based on the kinematics and dynamics of vehicles to improve the precision of a driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…To make an existing dump truck operate automatically, it is required to operate the steering wheel, accelerator pedal, and brake pedal of the dump truck in some way. In some studies, dump trucks are directly operated by controlling their hydraulic system [8,9]. However, this mechanism of operation is difficult for users because construction machinery manufacturers do not disclose vehicle information.…”
Section: Related Workmentioning
confidence: 99%
“…To make an existing dump truck operate automatically, it is required to operate the steering wheel, accelerator pedal, and brake pedal of the dump truck in some way. In some studies, dump trucks are directly operated by controlling their hydraulic system [8,9]. However, this mechanism of operation is difficult for users because construction machinery manufacturers do not disclose vehicle information.…”
Section: Related Workmentioning
confidence: 99%
“…The necessity of using more advanced models of articulated vehicles and a hydraulic steering system was confirmed [3]. Widely used linear models show relatively low accuracy and are not suitable for solving stability problems.…”
Section: Introductionmentioning
confidence: 99%
“…Lopatka et al [2] indicated that this speed for articulated vehicles is mainly limited by the snaking phenomenon-low direction stability of machine movement. According to Meng et al [3], the average speed of an articulated hauler on construction sites is about 25 km/h, with a top speed of 54 km/h. According to previous studies [2,4,5], low directional stability demands higher effort from drivers, increasing their concentration levels; additionally, cases of dynamic loads on bearings in joints and in the hydraulic cylinder are a serious problem.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the precision of the steering system model of the LHD machine, Meng et al 27 proposed fusion modeling method using its kinematics and dynamics. The complete kinematic steering model based on geometric relations, dynamic steering model considering forces acting at the each component and modeling of hydraulic subsystem using pressure flow equations of the articulated LHD vehicle has been developed.…”
Section: Introduction To Steering Systemsmentioning
confidence: 99%